Die Verklärung Jesu nach dem Markusevangelium Studien zu einer christologischen Legitimationserzählung - Wypadlo, Adrian (Mohr Siebeck, 2013)
The Transfiguration of Jesus in the Gospel of Mark. Studies of a Christological Legitimation Narrative.The Transfiguration of Jesus in the Gospel of Mark. Studies of a Christological Legitimation Narrative.
PublicationDate: 20130625
Keywords: Markusevangelium -- Christologie -- Transfiguration -- Verklärung -- Lohn -- Neues Testament -- Array